OIDC4AC: Extending OpenID Connect for Structured and Negotiable Authentication Contexts - Silva, Brendon Vicente R.; Schardong, Frederico; Custódio, Ricardo F. (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2026)
OpenID Connect (OIDC) is a widely adopted authentication protocol on the web. Despite its popularity, it provides limited expressiveness for describing how users are authenticated, constraining its applicability in high-assurance, auditable scenarios. To understand the extent of this gap, a Multivocal Literature Review was conducted, revealing the absence of an integrated, OIDC-native model for representing factors and specifying authentication requirements. To address these gaps, this paper proposes OpenID Connect for Authentication Context (OIDC4AC), a new OIDC protocol extension that enables fine-grained specification and detailed representation of authentication factors, improving interoperability and auditability.